Sosialisasi Pembukuan Keuangan Menggunakan Aplikasi BukuWarung bagi Pelaku Usaha Warung Sembako di Desa Cisitu Kabupaten Serang Banten - Yoki Yusanto (Jurnal Pengabdian UNDIKMA, 2022)
This socialization aims as a service to the community to provide understanding to the food stall business actors about the importance of recording or accounting for their activities and business progress, and introducing the BukuWarung application to the food stall business actors in Cisitu Village. The method used in this outreach is the survey method, socialization and training for food stall business actors. The results obtained from the survey results show that there are still basic food stalls that have not recorded or recorded and most of those who do bookkeeping are still unstructured, because they still mix the results of sales and purchases. In carrying out the extension of the BukuWarung application, business owners get information and understanding about the BukuWarung application. In this socialization activity, the owner of the shop began to try the application on his Android mobile phone.